Radiometric measurements of the microwave emissivity of foam - Knapp, E. J., author; Farquharson, G., author; Horgan, Kevin A., author; Dowgiallo, D. J., author; St. Germain, K. M., author; Gaiser, Peter W., author; Reising, Steven C., author; Asher, William E., author; Rose, Louis Allen, author; IEEE, publisher (Colorado State University. Libraries, 2002)
Radiometric measurements of the microwave emissivity of foam were conducted during May 2000 at the Naval Research Laboratory's Chesapeake Bay Detachment using radiometers operating at 10.8 and 36.5 GHz. Horizontal and vertical polarization measurements were performed at 36.5 GHz; horizontal, vertical, +45°, 45°, left-circular, and right-circular polarization measurements were obtained at 10.8 GHz. These measurements were carried out over a range of incidence angles from 30° to 60°. Surface foam was generated by blowing compressed air through a matrix of gas-permeable tubing supported by an aluminum frame and floats. Video micrographs of the foam were used to measure bubble size distribution and foam layer thickness. A video camera was boresighted with the radiometers to determine the beam-fill fraction of the foam generator. Results show emissivities that were greater than 0.9 and approximately constant in value over the range of incidence angles for vertically polarized radiation at both 10.8 and 36.5 GHz, while emissivities of horizontally polarized radiation showed a gradual decrease in value as incidence angle increased. Emissivities at +45°, 45°, left-circular, and right-circular polarizations were all very nearly equal to each other and were in turn approximately equal to the average values of the horizontal and vertical emissivities in each case.
Keywords: microwave radiometry; foam; emissivity; polarimetry